Gut contents of common house gecko, Hemidactylus frenatus (Schlegel, 1836) in Jahangirnagar university campus, Savar, Bangladesh - Naher, Kamrun; Alam, ABM Sarowar; Rahman, Shahriar; Kabir, Md Mofizul (Bangladesh Journal of Zoology, 2015)
Gut contents of Common House Gecko (Hemidactylus frenatus) collected from Jahangirnagar University campus, Savar, Dhaka were analysed. Sixteen different food items were identified of which most were insects. Insects from the order Orthoptera were the highest (32.66%) followed by the Coleopterans (18.36%), Diptera (14.28%), Hymenoptera (10.20%), Homoptera (10.20%), Lepidoptera (8.16%) and Hemiptera (6.14%). It is evident that the H. frenatus plays an important role in biological pest control consuming 39.13% insects which are harmful to crops, fruits and vegetables; 19.56% insects responsible for plant damage, 8.56% insects injurious to cotton, 6.52% garden pests, 6.52% were house hold pests, 4.32% destructive to plant seeds and roots of beans and cereals and remaining 15.21% were useful insects. Female consumed more than males. Bangladesh J. Zool. 41(2): 229-232, 2013